Say You'll Remember Me - Jimenez, Abby (New York, 2025)
"There might be no such a thing as a perfect guy, but Xavier Rush comes disastrously close. A gorgeous veterinarian giving Greek god vibes-all while cuddling a tiny kitten? Immediately yes. That is until Xavier opens his mouth and proves that even sculpted gods can say the absolute wrong thing. Like, really wrong. Of course, there's nothing Samantha loves more than proving an asshole wrong... . . . unless, of course, he can admit he made a mistake. But after one incredible and seemingly endless date-possibly the best in living history-Samantha is forced to admit the truth, that her family is in crisis and any kind of relationship would be impossible. Samantha begs Xavier to forget her. To remember their night together as a perfect moment, as crushing as that may be. Only no amount of distance or time is nearly enough to forget that something between them. And the only thing better than one single perfect memory is to make a life-and even a love-worth remembering"--
Keywords: Novels; Romance fiction